Concentrations and loadings of alkanes in surface sediments of Helgoland Mud Area in the North Sea - Bingbing Wei; Moritz Holtappels (PANGAEA, 2025)
Surface sediment were extracted 4 times by ultrasonication with dichloromethane: methanol (9:1, v/v) for 15 min for FAs and alkanes. For quantification of FAs and alkanes, known amounts of 19-methylarachidic acid and squalane were added as internal standards prior to extraction. Supernatants from each extraction were obtained by centrifugation and combined. The total lipid extracts were concentrated and evaporated under a nitrogen stream. The total lipid extracts were saponified for 2 h at 80 °C with 1 mL of KOH (0.1 M) in methanol: H2O (9:1, v/v). After saponification, the neutral fractions were liquid-liquid extracted with n-hexane and alkanes were eluted from the neutral fractions by silica gel column chromatography with n-hexane. The remaining KOH solution was acidified to pH 1, from which FA were liquid-liquid extracted into dichloromethane. The extracted and dried FAs were converted to methyl ester derivatives (FAMEs) in methanol: HCl (95:5, v/v) at 60 °C for 12 h. After methylation, the FAME fraction was further purified by silica gel column chromatography using dichloromethane: hexane (2:1, v/v) to remove residual polar compounds. FAMEs and alkanes were analyzed on a 7890A gas chromatograph (GC) equipped with a DB-5MS fused silica capillary column (60 m, 250 μm, 0.25 μm) and a flame ionization detector (FID). Peak areas were determined by integrating the respective peaks and concentrations were calculated against the internal standards. FAME contents were subsequently corrected for the derivative methyl carbon to determine FA contents. FAs and alkanes were normalized to OC content.
In: Wei, B; Holtappels, M (2025): Geochemical properties in surface sediments of the Helgoland Mud Area and surrounding sandy areas taken during HEINCKE cruise HE595 in the North Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.971520